1997
DOI: 10.1021/bi970422u
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Human Isovaleryl-CoA Dehydrogenase at 2.6 Å Resolution:  Structural Basis for Substrate Specificity,

Abstract: Isovaleryl-CoA dehydrogenase (IVD) belongs to an important flavoprotein family of acyl-CoA dehydrogenases that catalyze the alpha,beta-dehydrogenation of their various thioester substrates. Although enzymes from this family share similar sequences, catalytic mechanisms, and structural properties, the position of the catalytic base in the primary sequence is not conserved. E376 has been confirmed to be the catalytic base in medium-chain (MCAD) and short-chain acyl-CoA dehydrogenases and is conserved in all memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 35 publications
3
106
0
Order By: Relevance
“…PigA has good sequence identity with a wide range of acylCoA dehydrogenases. Sequence alignment with human isovaleryl-CoA dehydrogenase, the crystal structure of which has been determined, showed that the majority of amino acids around the flavin and the phosphopantetheinyl moiety of CoA are conserved but the amino acids involved in binding the adenosyl group of CoA are not conserved (Tiffany et al, 1997). This supports the suggestion that the substrate for PigA is a prolyl PCP rather than prolyl-CoA.…”
Section: Biosynthesis Of Mbcmentioning
confidence: 61%
“…PigA has good sequence identity with a wide range of acylCoA dehydrogenases. Sequence alignment with human isovaleryl-CoA dehydrogenase, the crystal structure of which has been determined, showed that the majority of amino acids around the flavin and the phosphopantetheinyl moiety of CoA are conserved but the amino acids involved in binding the adenosyl group of CoA are not conserved (Tiffany et al, 1997). This supports the suggestion that the substrate for PigA is a prolyl PCP rather than prolyl-CoA.…”
Section: Biosynthesis Of Mbcmentioning
confidence: 61%
“…wrote the paper. (19), isovaleryl acyl-CoA dehydrogenase (IVD, PDB ID code 1IVH) (18), acyl-CoA oxidase II (ACO, PDB ID code 1IS2) (9), and nitroalkane oxidase (NAO, PDB ID code 2C0U) (26). AidB residues important for tetramerization and DNA binding are highlighted gray and black, respectively, and those predicted to contact DNA are marked with black triangles.…”
Section: Resultsmentioning
confidence: 99%
“…3) (10). It has been proposed that the glycine in this position in IVD allows for binding branched acyl chains (8,18). In addition to the Trp-424 steric block, the 5-Å displacement of the Glu-425 carboxylate from its normal position in ACADs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The selfrotation function has only point-groupspeci®c peaks, but the native Patterson map calculated for 10±4 A Ê data has a weak but signi®cant 9' translational symmetry peak at (0.32, 0.68, 0.61) and a 7' peak at (0.67, 0.33, 0.25). Attempts to solve the structure of ACX4 by molecular replacement using the complete structures or domains from medium-chain acyl-CoA dehydrogenase (Kim et al, 1993), buturyl-CoA dehydrogenase (Djordjevic et al, 1995), isovaleryl dehydrogenase (Tiffany et al, 1997) or shortchain acyl-CoA dehydrogenase (Battaile et al, 2002) were unsuccessful. The sequence identity between A. thaliana ACX4 and the ACADs is only $20%, while its identity to other ACXs is below 15%, making the selection of a common structural motif dif®cult.…”
Section: Resultsmentioning
confidence: 99%